2009
DOI: 10.1111/j.1439-0388.2008.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism of 5′ flanking region of prolactin gene and its association with litter size in sheep

Abstract: A single nucleotide polymorphism of 5' flanking region of the prolactin gene was investigated in both high prolificacy breeds (Small Tail Han and Hu sheep) and low prolificacy breeds (Dorset and Suffolk sheep) using polymerase chain reaction (PCR)-single strand conformation polymorphism (SSCP). The results indicated that two genotypes (AA and AB) were detected in Small Tail Han sheep (n = 239), only one genotype (AA) was detected in Hu (n = 40), Dorset (n = 50) and Suffolk sheep (n = 39). The mutant homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Two genes ( MAPK14 and ANTXR2 ; Hancock et al 2008 ; Fumagalli et al 2011 ) were previously detected to be associated with regional variations in climate and pathogens in humans ( supplementary table S6 , Supplementary Material online). In addition, only six genes were associated with growth and production ( POL and LRRC2 ; Zhang et al 2013 ), reproduction ( FSHR and PRL ; Rannikki et al 1995 ; Chu et al 2007 , 2009 , 2012 ), coat color ( EDNRB ; Metallinos et al 1998 ; Wilkinson et al 2013 ), and fat deposits ( ACSS2 ; Bichi et al 2013 ), as identified by earlier genetic studies in sheep ( supplementary tables S5 and S7 , Supplementary Material online) and other livestock.…”
Section: Resultsmentioning
confidence: 70%
“…Two genes ( MAPK14 and ANTXR2 ; Hancock et al 2008 ; Fumagalli et al 2011 ) were previously detected to be associated with regional variations in climate and pathogens in humans ( supplementary table S6 , Supplementary Material online). In addition, only six genes were associated with growth and production ( POL and LRRC2 ; Zhang et al 2013 ), reproduction ( FSHR and PRL ; Rannikki et al 1995 ; Chu et al 2007 , 2009 , 2012 ), coat color ( EDNRB ; Metallinos et al 1998 ; Wilkinson et al 2013 ), and fat deposits ( ACSS2 ; Bichi et al 2013 ), as identified by earlier genetic studies in sheep ( supplementary tables S5 and S7 , Supplementary Material online) and other livestock.…”
Section: Resultsmentioning
confidence: 70%
“…Moreover, the association analyses revealed the PRL-P1-ins-23 bp indel within the PRL gene significantly associated with first parity and average litter sizes (p < .05). The studies of various authors have established that SNP variants within the PRL gene were related to the litter size in sheep (Chu et al, 2009;Jawasreh, Jadallah, & Al-Massad, 2017). For example, Chu et al (2009) identified an association between SNP mutation in the 5′ flanking region of the prolactin gene and litter size in Small tail Han sheep (Chu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…La prolactina es una hormona polipeptídica de la pituitaria anterior, involucrada en muchos procesos endocrinos esenciales para un adecuado comportamiento reproductivo (69) . Su acción es mediada por su receptor (PRLR), cuyo gen es miembro de la familia del receptor de la hormona de crecimiento/prolactina, el cual contiene regiones con secuencias idénticas (70) .…”
Section: Gen Del Receptor De Prolactina (Prlr)unclassified
“…Prolactin (PRL) is a polypeptide hormone of the anterior pituitary, involved in many endocrine processes essential for an adequate reproductive behaviour (69) . Its action is mediated by its receptor (PRLR), whose gene is member of the prolactin/growth hormone receptor family, which contains regions with identical sequences (70) .…”
Section: Prolactin Receptor Gene (Prlr)mentioning
confidence: 99%